2015
DOI: 10.12659/pjr.892341
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound (HIFU) in Localized Prostate Cancer Treatment

Abstract: SummaryBackgroundHigh-intensity focused ultrasound (HIFU) applies high-intensity focused ultrasound energy to locally heat and destroy diseased or damaged tissue through ablation. This study intended to review HIFU to explain the fundamentals of HIFU, evaluate the evidence concerning the role of HIFU in the treatment of prostate cancer (PC), review the technologies used to perform HIFU and the published clinical literature regarding the procedure as a primary treatment for PC.Material/MethodsStudies addressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 70 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…The instantaneous high temperature generated by HIFU denatures the tissue, leading to coagulative necrosis, and the free radicals generated also promote the decomposition of cells at the same time. In addition, high-amplitude mechanical waves inactivate cells, and chemical reactions of chemical components in the membrane structure under the action of high-energy ultrasound also promote cell death [2123]. When energy is concentrated in the submucosa of the nasal cavity, the death of immune cells reduces the release of cytokines and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The instantaneous high temperature generated by HIFU denatures the tissue, leading to coagulative necrosis, and the free radicals generated also promote the decomposition of cells at the same time. In addition, high-amplitude mechanical waves inactivate cells, and chemical reactions of chemical components in the membrane structure under the action of high-energy ultrasound also promote cell death [2123]. When energy is concentrated in the submucosa of the nasal cavity, the death of immune cells reduces the release of cytokines and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…However, in several pre-clinical studies addressing the combination of radio- and immuno-therapies to improve therapeutic potential [ 78 ], it has been shown that necrotic cell death can increase tumour immunogenicity through induction of heat shock protein expression [ 79 ]. Moreover, necrosis is induced by thermally ablative treatments such as cryotherapy [ 80 ], radiofrequency ablation [ 81 ] and HIFU [ 82 ], and is known to cause local inflammation at the treatment site. As mentioned previously, it has recently been demonstrated that prostate cancer cells cultured directly from patient tissue samples and treated with LTP rapidly initiate necrotic cell death [ 17 ].…”
Section: Combination Of Ltp Treatment With Existing Cancer Therapiesmentioning
confidence: 99%
“…Despite these safety measures, a review of the literature reported multiple adverse events among patients using HIFU as a primary therapy option in prostate cancer. Adverse events included bladder neck/urethral stenosis/stricture (2–17%), prolonged urinary retention (3–14%), urinary tract infection (2–58%), urinary incontinence (2–34%), rectal burns (0–15%), and rectourethral fistula (0–3%) [ 10 ]. In the same setting, our patient had urinary obstructive symptoms in addition to perianal pain caused by a necrosis of the levator ani that eventually resolved while maintaining residual pain.…”
Section: Discussionmentioning
confidence: 99%